Needs Analysis of STEAM Based E-LKPD to Enhance Learning Independence of Grade IV Elementary Students - Yunita Miftahul Jannah; Ika Febriana Wati; Dhesta Youlandi Rahayu Sulistiyawati; Ilham Fatkhu Romadhon; Rinda Angghita Putri (STEAM Journal For Elementary School Education, 2026)
Learning independence is an essential competency in the Merdeka Curriculum. However, in practice, grade IV elementary school students still demonstrate a fairly high dependence on their classroom teachers, particularly in science learning on the topic of changes in the state of matter. This study aims to analyze the need for developing a STEAM based E-LKPD to enhance the learning independence of grade IV students at SDN 1 Wonocoyo. The method used in this study was a preliminary study with a descriptive qualitative and quantitative approach. The research subjects included one grade IV teacher and students at SDN 1 Wonocoyo. Data collection instruments consisted of interview guidelines, student needs questionnaires, learning observation sheets, and documentation studies. The analysis yielded three main findings. First, from the teacher's perspective, the available worksheets were still dominated by memorization questions and had not integrated the five aspects of STEAM. Second, from the student's perspective, 85% of respondents stated that they were more interested in interactive digital media and experienced difficulty understanding the concepts of changes in the state of matter in the absence of visual simulations. Third, from the perspective of learning independence, 78% of students at SDN 1 Wonocoyo were not yet able to manage their own learning strategies because reflection was rarely practiced and they tended to be passive, waiting for teacher instructions. Based on these three findings, it can be concluded that the development of a STEAM based E-LKPD is highly necessary, with key features including interactive simulations on the topic of changes in the state of matter, accompanied by self-reflection rubrics, collaborative project activities, and practical guides for teachers. The results of this needs analysis serve as an important foundation for the subsequent design and development stages of the product at SDN 1 Wonocoyo.